THE EFFECT OF INITIAL ARCHWIRES SELECTION ON ORTHODONTIC TREATMENT EFFICIENCY AND OUTCOME - Kocevski, Stefana Chakar; Kanurkova, Lidija (Journal of Morphological Sciences, 2023)
Initial orthodontic archwires perform the desired tooth movements in the phase of alignment and leveling during the fixed orthodontic treatment by applying force to the teeth. The force should be light and continuous which will result in maximum tooth movement, with minimal root resorption and pain. This literature review aims to explore the current knowledge about initial orthodontic archwires. A literature search was conducted on the following electronic databases: PubMed, Cochrane Library, and Google Scholar, as well as grey literature sources, were reviewed. The search resulted in the selection of relevant peer-reviewed articles, clinical trials as well as academic sources such as textbooks, that provide a comprehensive overview of the topic. The review highlights the importance of selecting the appropriate archwire material, wire size, and shape for optimal and predictable orthodontic treatment outcomes. It also emphasizes the impact of these variables on force generation in order treatment optimization. Lastly, discuss the advantages and disadvantages of archwire customization, a current global trend that should provide better treatment outcomes in a shorter period of time and improved patient comfort. Overall, careful selection of initial archwire is important in achieving successful treatment outcomes customized per patient needs and treatment goals. Key words: orthodontic wires, alloys, elastic modulus, orthodontic force. https://doi.org/10.55302/JMS2361163chk